Analysing social policy concepts and language : comparative and transnational perspectives - Béland, Daniel; Petersen, Klaus, 1965- (Policy Press, 2014)
Where do concepts such as "welfare state" and "social security" come from and how does their meaning changed over time. This edited collection, written by a cross-disciplinary group of leading social policy researchers, analyses the concepts and language used to make sense of contemporary social policy